The Application of Numerical Study for Dynamic Vibration Absorber in Suspension System to Improve Four Wheel Vehicle Comfort - Hafizah, Hafizah; Mainil, Rahmat Iman; Nazaruddin, Nazaruddin; Abdurrahman, Ridwan (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
This study aims to develop a Dynamic Vibration Absorber (DVA) for a four-wheeled vehicle, specifically the "Toyota Fortuner 4.0 V6 SR" model. The quarter vehicle structure was modeled as a two degree of freedom system with disturbances in the form of road contours and speed. The natural frequency of the DVA was designed to be equal to the lowest natural frequency of the vehicle. Hence, if the vehicle moved at a speed or road contour disturbance close to its natural frequency, the vibration energy will be transferred or received by the DVA so that the vehicle structure did not oscillate. Two DVAs were mounted on the top of the vehicle body. The results obtained the vibration that occurs when the disturbance frequency was closed to the lowest natural frequency of the ¼ vehicle structure. It was significantly reduced by the addition of two DVAs. The design model of the ¼ vehicle test structure and Dynamic Vibration Absorber (DVA) in this study can be used as a reference for the implementation of experiments. The results of experimental calculations can be compared with the results of theoretical calculations to strengthen the credibility of the results.